RNA sequencing and weighted gene co-expression network analysis uncover the hub genes controlling cold tolerance in Helictotrichon virescens seedlings - Cheng, Mingjun; Pan, Zeyang; Cui, Kuoshu; Zheng, Junjun; Luo, Xuan; Chen, Youjun; Yang, Tao; Wang, Hui; Li, Xiaofeng; Zhou, Yang; Lei, Xiong; Li, Yingzheng; et al. (Frontiers in Plant Science, 2022)
Helictotrichon virescens is a perennial herbaceous plant with a life expectancy of about 10 years. It has high cold and heat resistance and can successfully survive over winter in the habitats with a temperature range of -25 ℃ to 25 ℃. Therefore, this study aimed to identify the key genes regulating low-temperature stress responses in H. virescens and analyze cold tolerant at molecular level. This study used RNA sequencing (RNA-Seq) and weighted gene co-expression network analysis (WGCNA) to identify the hub genes associated with cold tolerance in H. virescens. RT-PCR was conducted, Homologous genes were identified, and related bioinformatics were analyzed to verify the identified hub genes. Moreover, WGCNA analysis showed that only the brown module had the highest correlation with the active-oxygen scavenging enzymes (POD, SOD, and CAT). The expression levels of three hub genes in the brown module (Cluster-37118.47362, cluster-37118.47713, and cluster-37118.66740) were significantly higher under low-temperature stress than those under control conditions. Furthermore, GO and KEGG annotations showed that the 3 hub genes were mainly enriched in the metabolism pathways of sphingolipids, selenocompounds, glyoxylate, and dicarboxylate, carotenoids biosynthesis, and other biological pathways. The results of this study also showed that the subcellular localization prediction results showed that the cold tolerance hub genes were all localized to the plasma membrane. By constructing a protein interaction network, it was found that the hub gene Cluster-37118.66740 interacted with Sb09g003460.1 and Sb04g020180.1 proteins in Sorghum bicolor. By constructing phylogenetic trees of the four species of H. virescens, Sorghum bicolo, Oryza sativa Japonica and Arabidopsis thaliana, the results showed that, the hub gene Cluster 37118.66740 (of H. virescens) and Os03g0340500 (of Oryza sativa Japonica) belonged to the same ancestral branch and were in the same subfamily. Thus, this study provide methodology and guidance to identify the cold tolerance genes for other herbage and their cold tolerant molecular mechanisms at molecular level.